PENGELOLAAN KAWASAN KARST Dl KALIMANTAN TIMUR - Sugiyanto, Bambang (Balai Arkeologi Kalimantan Selatan, 2008)
There are still some flaws in cultural resource management in Indonesia, especially in regard to cultural heritage management in karst environment. It is necessary to establish a good coordination and cooperation on archaeological resource management in the karst environment between the departments and district governments of: Culture and Tourism, Forestry, Environment, Mineral and Energy. A excellent system of coordination and cooperation in respect to archaeological resource management in karst environment is well represented in East Kalimantan.